1998
DOI: 10.1093/oxfordjournals.pcp.a029365
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cycles of Dormancy and Growth in Pea Axillary Buds Based on mRNA Accumulation Patterns of Cell Cycle-Related Genes

Abstract: Axillary buds of pea (Pisum sativum L. cv. Alaska) do not grow on intact plants. Dormant axillary buds can be stimulated to grow rapidly after decapitation. Here, we isolated cDNAs of PCNA, cyclinB, cyclinD, and cdc2 from pea. The mRNA expression levels of these genes were very low in dormant axillary buds, whereas they remarkably increased after decapitation. Based on the mRNA accumulation patterns of these genes, we found that most cells in dormant axillary buds are arrested at the Gi phase in the cell cycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(53 citation statements)
references
References 28 publications
2
50
0
1
Order By: Relevance
“…To investigate whether the loss of apical dominance of bud2 plants involves auxin action, we examined the hypocotyl elongation at higher temperature and the lateral shoot development after decapitation of wild-type and bud2 mutant plants [43,57,58]. Identification of temperatureinduced hypocotyl elongation is a simple and rapid assay in the study of an auxin-mediated growth response [59].…”
Section: The Bud2 Plant Shows Altered Hypocotyl Elongation and Lateramentioning
confidence: 99%
“…To investigate whether the loss of apical dominance of bud2 plants involves auxin action, we examined the hypocotyl elongation at higher temperature and the lateral shoot development after decapitation of wild-type and bud2 mutant plants [43,57,58]. Identification of temperatureinduced hypocotyl elongation is a simple and rapid assay in the study of an auxin-mediated growth response [59].…”
Section: The Bud2 Plant Shows Altered Hypocotyl Elongation and Lateramentioning
confidence: 99%
“…These dormant axillary buds resume development at a later time depending on their developmental program or in response to environmental cues. The cycles between dormancy and growth in axillary buds were characterized using the garden pea (Stafstrom and Sussex, 1992;Devitt and Stafstrom, 1995;Shimizu and Mori, 1998a). The second node of pea plants has four dormant axillary buds, and all of the axillary buds are different sizes.…”
Section: Development and Potential Of Axillary Meristemsmentioning
confidence: 99%
“…Analyses of the mitotic index indicated that removal of the terminal bud rapidly promotes cell division in axillary buds (Martin, 1987). In pea axillary buds, the proliferating and quiescent (phase of the cell cycle in which the dormant bud cells are arrested) cell cycles are characterized by mRNA accumulation patterns of several cell cycle-related genes (Devitt and Stafstrom, 1995;Shimizu and Mori, 1998a). These gene transcripts accumulate in a cell cycle-specific fashion.…”
Section: Molecular Approachmentioning
confidence: 99%
“…Indeed, dormant buds are highly developed and would presumably require vascular connections for early development and growth before they enter a stage of dormancy. Additionally, buds could become active and later reenter a stage of dormancy (Stafstrom and Sussex, 1992;Shimizu and Mori, 1998). In contrast to these findings, Sorokin and Thimann (1964) reported that xylem strands from an axillary bud did not connect with those from the main stem until after release from apical dominance.…”
mentioning
confidence: 93%